Future prospects in the treatment of erectile dysfunction: focus on avanafil - Alwaal A; Al-Mannie R; Carrier S (Dove Medical Press, 2011)
Amjad Alwaal, Raed Al-Mannie, Serge Carrier Division of Urology, McGill University Health Centre, Montreal, Quebec, Canada Abstract: The treatment of erectile dysfunction (ED) has been revolutionized in the last 15 years with the introduction of type 5 phosphodiesterase (PDE5) inhibitors. Their efficacy, safety, and ease of administration have made them first-line treatment for ED. This article reviews the current therapies available for ED, and the new PDE5 inhibitors that are being investigated. Furthermore, it examines all the current ED treatment options that are in different phases of development (including oral and topical pharmacotherapy, gene therapy, and tissue engineering). A special emphasis is on avanafil, a new PDE5 inhibitor that has been studied extensively in Phase I and II clinical trials and has undergone several Phase III trials. Avanafil is a promising medication for ED due to its favorable pharmacokinetics, safety, and efficacy. Keywords: PDE5, sexual performance, pharmacokinetics